Psychological Resilience among a Sample of Mothers of Autistic Children in the City of Sebha "A Field Study on a Sample of Mothers of Autistic Children at the Al-Safa Center for Mental Health in the City of Sebha" (Journal of Human Sciences, 2021)
The current study was conducted to identify the level of psychological resilience of a sample of mothers with autistic children in the City of Sebha. It is done in the light of some demographic variables such as "age, educational level, number of children, years of marriage". The descriptive-analytical approach was used in this study. The psychological resilience scale prepared by the researcher (Kenz Dallah) was applied to a sample of 50 mothers of autistic children. They were chosen intentionally from mothers of autistic children who regularly visited the Safaa Center for Mental Health in Sebha. This is done to find out whether the mothers enjoy psychological resilience or not. After analyzing the data using appropriate statistical methods, including analysis of variance to find out the differences, and the “T” test for independent samples, the results concluded that there is no psychological resilience among mothers of autistic children. There are also no statistically significant differences in the average degrees of psychological resilience among A sample of mothers of autistic children. This is happening due to the variables of age, the number of children, educational level and years of marriage.